Faster players slower to recover after training and competition, with possible adverse effects on football performance - Gastin, P.; Fahrner, B.; Meyer, D.; Robinson, D.; Cook, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Speed and speed endurance are positively related to success in the football codes and are often included in talent identification and selection criteria of players (Reilly and Gilbourne 2003; Pyne, Gardner et al., 2005). These desirable characteristics, however, may predispose the player to greater post training and competition muscle damage (Paddon-Jones, Keech et al. 2005), potentially affecting the time course of recovery and performance in the next game. To explore this hypothesis, performance data routinely collected in a professional Australian Rules football club were analysed to assess the influence of selected player characteristics on recovery and playing performance. Methods: Data were collected over a full competition season from a squad of 27 professional Australian Rules football players. Player characteristics assessed during the pre-season, including maximal speed over 40 m and time to complete six 40 m sprints (speed endurance), were used as moderating variables in hierarchical linear modelling of the data. The first analysis considered trends over the week in player self-ratings on six physical wellness items (general muscle, quadriceps and hamstring strain, fatigue, pain/stiffness, power). The second analysis explored the relationship between training load and weekly performance from playing statistics. Results: A total of 2,583 self-rating questionnaires were analysed from completions on 183 days throughout the season. Ratings for all physical wellness items were worse in the days immediately post competition, improving steadily over the week to a game day low. Four of the six physical items (muscle, hamstring and quadriceps strain, power; p<0.01) were slower to recover for players with high maximal speed. In the second analysis, player speed endurance was found to have a significant moderating effect (p<0.05) on the relationship between weekly training load and playing performance. Game performance in players who performed well on the six 40 m sprint test was adversely affected when training load increased above the mean. Discussion: Analysis of self-ratings of wellness indicates that players with high maximal speed take longer to physically recover from weekly competition. Furthermore, players with good speed endurance find that their playing performance is adversely affected following a week when the main training session is heavier in load than usual. The practical implications of these finding are that players with high maximal speed need to be particularly diligent with recovery practices in the days following competition and heavy training sessions and may need to be protected from heavy intense training in the middle of the week.